The Amide Local Anesthetic Lidocaine in Cancer Surgery—Potential Antimetastatic Effects and Preservation of Immune Cell Function? A Narrative Review - Chamaraux-Tran, Thiên-Nga; Piegeler, Tobias (Frontiers in Medicine, 2017)
Surgical removal of the primary tumor in solid cancer is an essential component of the treatment. However, the perioperative period can paradoxically lead to an increased risk of cancer recurrence. A bimodal dynamics for early-stage breast cancer recurrence suggests a tumor dormancy-based model with a mastectomy-driven acceleration of the metastatic process and a crucial role of the immunosuppressive state during the perioperative period. Recent evidence suggests that anesthesia could also influence the progress of the disease. Local anesthetics (LAs) have long been used for their properties to block nociceptive input. They also exert anti-inflammatory capacities by modulating the liberation or signal propagation of inflammatory mediators. Interestingly, LAs can reduce viability and proliferation of many cancer cells in vitro as well. Additionally, retrospective clinical trials have suggested that regional anesthesia for cancer surgery (either with or without general anesthesia) might reduce the risk of recurrence. Lidocaine, a LA, which can be administered intravenously, is widely used in clinical practice for multimodal analgesia. It is associated with a morphine-sparing effect, reduced pain scores, and in major surgery probably also with a reduced incidence of postoperative ileus and length of hospital stay. Systemic delivery might therefore be efficient to target residual disease or reach cells able to form micrometastasis. Moreover, an in vitro study has shown that lidocaine could enhance the activity of natural killer (NK) cells. Due to their ability to recognize and kill tumor cells without the requirement of prior antigen exposure, NKs are the main actor of the innate immune system. However, several perioperative factors can reduce NK activity, such as stress, pain, opioids, or general anesthetics. Intravenous lidocaine as part of the perioperative anesthesia regimen would be of major interest for clinicians, as it might bear the potential to reduce the risk of cancer recurrence or progression patients undergoing cancer surgery. As a well-known pharmaceutical agent, lidocaine might therefore be a promising candidate for oncological drug repurposing. We urgently need clinical randomized trials assessing the protective effect of lidocaine on NKs function and against recurrence after cancer surgery to achieve a “proof of concept.”